Evaluation and implementation of a 5-level hybrid DC-DC converter - El-Sehrawy, Farid Khaled (AUC Knowledge Fountain, 2015)
In this work, a hybrid voltage regulator topology is analyzed, implemented, and evaluated. The common topologies of DC-DC converters have proven to be lacking in some aspects, such as integrability for buck converters, or maximum efficiency for switched-capacitor regulators. The hybrid topology tackles these shortcomings by combining the advantages of switched-capacitor and inductor-based voltage regulators. A 5-level buck converter is evaluated, implemented, and compared to other converter implementations using the same components. The 5-Level Buck converter can achieve 5 different levels, allowing it to cover 4 operation regions, each between 2 levels. Accordingly, it covers a wide range of output voltages. By reducing the voltage difference at the inductor input, the 5-level buck converter can use smaller inductor compared to both 3-level and conventional buck converters which makes it cheaper, smaller in size, and much more efficient. Simulations show proper functionality of the 5-Level topology, while putting restrictions on the inductor size, efficiency, and component footprint (or total converter area). A test PCB is implemented for verification of the functionality and experimental measurements show that for the same switching frequency and inductor size, the 5-level buck converter achieves up to 15% efficiency improvement over a conventional buck converter and a 3-level buck converter at certain output voltage ranges. Peak efficiency of 94% has been achieved by the 5-Level hybrid converter, which includes all external switching and conduction losses. The proposed hybrid topology proved to yield high conversion efficiency even in the face of component size limitations, which indicates potential benefit in using multilevel converters for several off-chip as well as on-chip applications.